2-D isotropic negative refractive index in a N-type four-level atomic system - Zhao Shun-Cai; Wu Qi-Xuan; Ma Kun (Open Physics, 2015)
2-D(Two-dimensional) isotropic negative refractive index (NRI) is explicitly realized via the orthogonal signal and coupling standing-wave fields coupling the Ntype four-level atomic system. Under some key parameters of the dense vapour media, the atomic system exhibits isotropic NRI with simultaneous negative permittivity and permeability (i.e. left-handedness) in the 2-D x-y plane. Compared with other 2-D NRI schemes, the coherent atomic vapour media in our scheme may be an ideal 2-D isotropic NRI candidate and has some potential advantages, significance or applications in the further investigation.